Cognitive functioning in patients with first-episode psychosis stratified by level of negative symptoms: A 1-year follow-up study. (November 2019) - Engen, Magnus Johan; Simonsen, Carmen; Melle, Ingrid; Færden, Ann; Lyngstad, Siv Hege; Haatveit, Beathe; Vaskinn, Anja; Ueland, Torill
Highlights: Longitudinal data were used to stratify FEP participants into negative symptom subgroups. Cognition and negative symptoms was closely related. Cognitive functioning in participants without negative symptoms was similar to healthy controls. The largest impairment was seen for participants with sustained negative symptoms. Abstract: We investigate negative symptoms over a 1-year follow-up period with the objective to see how groups defined according to level of symptom severity are related to cognition. Eighty-seven participants with first-episode psychosis (FEP) and matched healthy controls were assessed at baseline and follow-up. FEP participants were sub-grouped based on negative symptom items from the Positive and Negative Syndrome Scale (PANSS-R) with either no, mild, transitory or sustained symptoms over one year. Following an overall MANOVA, groups were compared on cognitive domains and a cognitive composite using ANOVAs. Cognitive course was explored with a MANOVA. We found a group effect on cognition. Participants who sustained negative symptoms were significantly outperformed by participants with no negative symptoms on executive functions and processing speed, and by those with mild or transitory symptoms on verbal learning and memory. Participants with sustained negative symptoms performed significantly poorer on the cognitive composite than those with no or mild negative symptoms. The group with no negative symptoms did not differ significantly from healthy controls on any cognitive measure, and the groups did not differ in cognitive course. Early course of negative symptoms is associated with cognition and could guide clinicians when evaluating need for cognitive assessment.